The Role of Service Quality and Customer Experience in Shaping Word-of-Mouth: The Mediating Effect of Customer Satisfaction on Cosmetic Products in Indonesia - Sugesti, Edwin (The Eastasouth Management and Business, 2025)
This study examines the relationships between service quality, customer experience, customer satisfaction, and word-of-mouth (WOM) in the context of cosmetic products in Indonesia, with a focus on the mediating role of customer satisfaction. Using a quantitative approach, data was collected from 250 respondents through a Likert scale questionnaire, and the data was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3). The results indicate that both service quality and customer experience significantly influence customer satisfaction, which in turn positively impacts WOM. Additionally, the study finds that service quality and customer experience have an indirect effect on WOM through customer satisfaction, highlighting the critical role of satisfaction in driving brand advocacy. These findings suggest that cosmetic brands should prioritize enhancing service quality and customer experience to improve customer satisfaction and encourage positive WOM, ultimately leading to stronger customer relationships and greater brand success.